2011
DOI: 10.1538/expanim.60.177
|View full text |Cite
|
Sign up to set email alerts
|

Gastric Hypomotility in Chronic Upper Gastrointestinal Disease of Japanese Macaques (Macaca fuscata)

Abstract: Japanese macaques bred indoor for laboratory use often show chronic anorexia and intermittent vomiting. In some of our macaques gastric air was observed on physical examination, and we suspected abnormality of gastric motility. We therefore performed contrast radiographic examinations of the gastrointestinal tract without anesthesia of 8 macaques with gastrointestinal symptoms and 9 asymptomatic controls from the same laboratory. Changes of abdominal radiography over time were observed following oral administr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 12 publications
0
3
1
Order By: Relevance
“…It has been reported that KTM does not majorly affect ECG parameters except HR. 26,41,42 In the present study, neither KTM nor TZ treatment resulted in any major changes in common electrocardiographic parameters of rhesus monkeys other than HR.…”
Section: Electrocardiographic Parameterscontrasting
confidence: 45%
See 2 more Smart Citations
“…It has been reported that KTM does not majorly affect ECG parameters except HR. 26,41,42 In the present study, neither KTM nor TZ treatment resulted in any major changes in common electrocardiographic parameters of rhesus monkeys other than HR.…”
Section: Electrocardiographic Parameterscontrasting
confidence: 45%
“…Mean HR values of KTM- and TZ-anesthetized groups were found to be significant upon comparison, wherein the mean heart rate of the KTM group was significantly lower than the HR of the TZ group of animals. Previously reported studies in Macaca mulatta sedated by KTM have reported mean HR values of 134 ± 15 bpm, while the mean HR from KTM-sedated Macaca fusucata 26 was 158 ± 20 and KTM-sedated Macaca fascicularis 41 were 168 ± 22 bpm. It has been observed that anesthetized animals, regardless of the choice of anesthetics, have displayed higher mean HR values.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Traditionally, the most common contact sensing tool for HR and RR measurement is an electrocardiogram (ECG) 8 . For example, ECG sensors were employed in NHPs, e.g., ECGs from monkeys under anesthesia 9 , 10 , an implanted sensor 11 , 12 , wearable jacket systems for non-sedated monkeys 13 .…”
Section: Introductionmentioning
confidence: 99%
“…In young infants or animals, placing the captor or maintaining it all throughout the experiment may turn out to be challenging if not impossible. In monkeys, recording HR either involves ECG or PPG under sedation [18][19][20] or implanting a telemetry device for HR measure during behaviour 21,22 . PPG recording or HR measures using captors embedded in a wearable jacket is also an option 11,23,24 .…”
mentioning
confidence: 99%